Design and fabrication of cost-effective heart-rate pulse monitoring sensor system - Zulkhairi Mohd Yusof; Md Masum Billah; Kushsairy Kadir; Nur Amanina; Nur Hidayah; Haidawati Nasir (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
A traditional approach of heart rate measurement has always meant that people must go to hospitals to examine the patient disease at Cardiologist and medical officer. Most people have difficult such as no transport and lazy to go to the hospital for the check-ups of their conditions heart rate. This is because, before have a treatment or medical check-up, they should do an appointment. Besides that, demands of works very high nowadays. People busy with their works until forget to do medical check-ups. Additionally, the available portable heart rate monitoring machine is costly to buy for all. In this research, we develop a system which can be accommodate for all while everyone can do their check up at home and do not waste their time by waiting for their turn in the hospital to do the medical check-ups. The prototype is built using low cost electronics components. The prototype can do a self-check-up before seeing a medical practitioner may reduce mortality rate due to the silent killer that is heart attacks.